Metal-carbon nanocatalysts for electrochemical CO2 reduction - Burwell, Tom (2025)
The work in this thesis investigates graphitised nanofibers as a support medium for metal catalysis for the electroreduction of CO2. They provide a nanotextured surface in which metal catalysts can be stabilised and the highly conductive properties of graphitised nanofibers and high surface area to volume ratio make them an ideal support for the electroreduction of CO2.